2015
DOI: 10.1186/s12890-015-0059-2
|View full text |Cite
|
Sign up to set email alerts
|

Whey peptide-based enteral diet attenuated elastase-induced emphysema with increase in short chain fatty acids in mice

Abstract: BackgroundSystemic inflammation is present in chronic obstructive pulmonary disease (COPD). A whey peptide-based enteral diet reduce inflammation in patients with COPD, but its effect on COPD development has not been determined. On the other hand, it is known that short chain fatty acids (SCFAs), which are produced by micro-flora in the gut, attenuates bronchial asthma in mice model.MethodsMice with elastase-induced emphysema were fed with 1 of 3 diets (control diet, whey peptide-based enteral diet, or standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…Our ndings suggest that the decrease in SCFA levels observed following exposure to BMF or MVE. Animal experiments also support this SCFA-related mechanism; an increase in dietary SCFAs was reported to attenuate the development of smoking-related emphysema in rats and mice [38,39]. We propose that SCFAs, and especially acetic acid, may confer a protective effect against PM-induced COPD.…”
Section: Discussionsupporting
confidence: 58%
“…Our ndings suggest that the decrease in SCFA levels observed following exposure to BMF or MVE. Animal experiments also support this SCFA-related mechanism; an increase in dietary SCFAs was reported to attenuate the development of smoking-related emphysema in rats and mice [38,39]. We propose that SCFAs, and especially acetic acid, may confer a protective effect against PM-induced COPD.…”
Section: Discussionsupporting
confidence: 58%
“…Oral Lactobacillus casei administration improved the previously defective function of peripheral natural killer cells in adult male smokers 91 , whereas Bifidobacterium breve and Lactobacillus rhamnosus reduced lung pathology in a mouse model of COPD 92 , and reduced inflammatory responses in macrophages exposed to cigarette smoke extract in vitro 93 . Similarly, a diet which increased SCFA production protected against elastase-induced inflammation and emphysema 94 .…”
Section: [H3] Microbiota and Copdmentioning
confidence: 97%
“…142 Furthermore, mice fed a peptide-based enteral diet that increased the production of SCFAs attenuated elastase-induced inflammation and emphysema in the lung. 143 The axis is by no means onedirectional, with respiratory infection driving perturbations in the gut microbiome, but further work is needed to validate this. 144,145 A study reported that the intranasal delivery of a non-absorbable tracer into the nasal cavity of mice appeared in the gastrointestinal tract shortly after.…”
Section: The Gutàlung Axismentioning
confidence: 99%